Creating a platform for collaborative genomic research. (2017) - Smithson, Mark; Frost, James; Williams, Julie; Simms, Rebecca; Majounie, Elisa; Kitchen, Christine; Badarinarayan, Nandini; Moreton, Andrew; Denning, Nicola; Bannister, Christian
No abstract available